2020
DOI: 10.1542/peds.2019-0741
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Treatment and Cardiovascular Risk Profile in Transgender Adolescents

Abstract: BACKGROUND AND OBJECTIVES: The effects of endocrinological treatment on cardiovascular risk profile in transgender adolescents are unknown. In this retrospective cohort study, we aim to investigate these effects and assess obesity and dyslipidemia prevalence in transgender adolescents at 22 years compared with peers. METHODS: Changes in BMI, systolic blood pressure (SBP), diastolic blood pressure (DBP), glucose, homeostatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 47 publications
1
64
0
1
Order By: Relevance
“…Two prospective observational studies conducted in Europe reported that BMI increased in transgender women after 12 months of GAHT [30] , [38] , [39] . Another longitudinal cohort study in transgender girls in Europe also reported a significant increase in BMI from the start of GAHT from a mean age of 15 years up to the age of 22 years [40] . However, other studies have not reported increases in BMI over a similar period of time [8] , [10] , [41] , although they have reported an increase in total body fat along with a significant decrease in lean body mass.…”
Section: Discussionmentioning
confidence: 86%
“…Two prospective observational studies conducted in Europe reported that BMI increased in transgender women after 12 months of GAHT [30] , [38] , [39] . Another longitudinal cohort study in transgender girls in Europe also reported a significant increase in BMI from the start of GAHT from a mean age of 15 years up to the age of 22 years [40] . However, other studies have not reported increases in BMI over a similar period of time [8] , [10] , [41] , although they have reported an increase in total body fat along with a significant decrease in lean body mass.…”
Section: Discussionmentioning
confidence: 86%
“…BMI was only slightly higher but the increase of obesity prevalence in transgender women was higher compared to cis-women. Thus, a subset of transgender women proved to be more prone for excessive weight gain [39]. In transgender men, body shape and body composition were within reference values for ciswomen and cis-men.…”
Section: Long-term Outcome Of Early Medical Interventionmentioning
confidence: 81%
“…The pre-treatment obesity prevalence was already higher compared to the general population, but the increase in prevalence was comparable to cis-men. For both transgender men and women, other cardiovascular risk factors such as fasting glucose, lipid profile, and blood pressure were similar or more favorable [39]. In addition, the psychological benefits of early medical intervention for young transgender adolescents have been established [30,31].…”
Section: Long-term Outcome Of Early Medical Interventionmentioning
confidence: 99%
“…Therapeutic phlebotomy or change of testosterone dose, interval, or preparation may also be considered. Androgenic alopecia ( 45 ), higher blood pressure ( 63 ), and mild reductions in high-density lipoprotein ( 63 , 64 ) have also been documented in some TGD adolescents using testosterone; a higher prevalence of obesity before and during testosterone therapy is also reported ( 64 ).…”
Section: Potential Side Effects Of Hormonal Interventionmentioning
confidence: 99%
“…To date, no significant differences in cardiovascular risk factors have been observed in association with hormonal therapies in TGD youth treated from adolescence to early adulthood ( 64 ). Nonetheless, encouraging universally endorsed lifestyle measures that promote cardiovascular health—such as physical activity, healthy body mass index (BMI), and avoidance of smoking and prolonged immobility—and ongoing clinical monitoring are recommended.…”
Section: Potential Side Effects Of Hormonal Interventionmentioning
confidence: 99%